الطبيعة القانونيـــــة للحقـــــــوق العماليــــــــــــــة ( آمريــــة الحقوق العماليــــة ) - رشيد, صبا نعمان; عبدالكريم, سرى محي (Journal of Legal Sciences, 2019)
The features of the phenomenon in legal thinking in the modern era the employment rules of criminal law in the public and private a like punishment for the crime of the property protected by the civil law .